Broadening the Scope of Enforced ATP Wasting as a Tool for Metabolic Engineering in Escherichia coli. Issue 9 (17th May 2019) - Boecker, Simon; Zahoor, Ahmed; Schramm, Thorben; Link, Hannes; Klamt, Steffen
Abstract : The targeted increase of cellular adenosine triphosphate (ATP) turnover (enforced ATP wasting) has recently been recognized as a promising tool for metabolic engineering when product synthesis is coupled with net ATP formation. The goal of the present study is to further examine and to further develop the concept of enforced ATP wasting and to broaden its scope for potential applications. In particular, considering the fermentation products synthesized by  Escherichia coli under anaerobic conditions as a proxy for target chemical(s), i) a new genetic module for dynamic and gradual induction of the F1 ‐part of the ATPase is developed and it is found that ii) induction of the ATPase leads to higher metabolic activity and increased product formation in E. coli under anaerobic conditions, and that iii) ATP wasting significantly increases substrate uptake and productivity of growth‐arrested cells, which is vital for its use in two‐stage processes. To the best of the authors' knowledge, the glucose uptake rate of 6.49 mmol gCDW −1  h −1 achieved with enforced ATP wasting is the highest value reported for nongrowing E. coli cells. In summary, this study shows that enforced ATP wasting can be used to improve yield and titer (in growth‐coupled processes) as well as volumetric productivity (in two‐stage processes) depending on which of the performance measures is more crucial for the process and product of interest. Abstract : The targeted increase of cellular adenosine triphosphate (ATP) turnover has recently been recognized as a promising tool for metabolic engineering. In this study, the authors further examine and further develop the concept of enforced ATP wasting for potential applications with  Escherichia coli . It is demonstrated that enforced ATP wasting can be used to improve yield and titer (in growth‐coupled processes) as well as glucose uptake and volumetric productivity (in two‐stage processes).